Tradisi Bali dalam Lipatan Kanvas Karya Seri Porosan I Ketut Sugantika ‘ Lekung’ - Budiaprilliana, Luh (Program Studi Seni Murni ISI Bali, 2022)
Tradition in the anthropological dictionary is the same as customs, whic is called the magical-religious habits of the life of an indigenous population which include cultural values, norms, laws and rules that are interrelated, and then become a system or regulations that have been established and include all conceptions of the cultural system of a culture to regulate social action (Arriyono and Siregar, 1985:4). The tradition that is strongly implemented in the environment where the child grows up has an influence in building the memory web of the child in his growth and development. I Ketut Sugantika 'Lekung' as one of the artists who was born and raised in Bali is one of the many artists who brings the memory web of Balinese traditions into their creative process. The Porosan series by I Ketut Sugantika 'Lekung' is a representation of Balinese tradition which is realized through the repetition of folds on canvas. The process of making which is full of repetitions with similar patterns presents a trance for the artist so that he feels a situation like he is meditating focusing on controlling the Tri Pramana which is consisting of Bayu, Sabda, and Idep.